"Śnić może?" O pustym wnętrzu ego, czyli prolegomena do krytyki cynicznej podmiotowości współczesnej - Nowak, Maciej (Er(r)go. Teoria - Literatura - Kultura, 2012)
Maciej Nowak “Perchance to dream?” On the Void Interior of Ego. A Prolegomenon to a Cynical Critique of a Contemporary Model of Subjectivity The text discusses interiority as the epistemic and ethical dimension of individual choices and responsibilities, possibly, the only bastion of subjective freedom in today’s furious reality (Salman Rushdie, Fury) in which contemporary models of life monitored by schematized, often televised, patterns of behaviour (Jerzy Kosinski, Being There) turn what once was called existence into an illusory idyll of consumerist vegetation. Following the reflexive path of psychoanalysis, the article reads the interiority of Hamlet and his quest for being (“to be”) as one of options which could be considered to be an indirect apology for empiricism and spiritual realisation in an environment, in which humanism and its values were appropriated by globalised, “cynical” ideology.